Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Multi-omics integration elucidates molecular mechanisms underlying distinctive meat quality in Liping cattle versus Angus hybrid and Simmental breeds - Longxin Xu; Xin Wang; Yuanfeng Zhao; Chunxia Zheng; Jing Liu; Kaikai Zhang; Wenzhang Zhou; Rong Yang; Di Zhou; Zhongling Jian; Yongcai Zhu; Junda Wu; et al. (Food Research International, 2026)

Environmental benzophenone exposure promotes liver cancer cell proliferation via the IRE1α-XBP1s pathway - Rong Wang; Jing Yang; Kailun Wang; Liwei Chen; Hongqing Zhou; Xia Sheng; Mei Zhao; Mingsheng Liu; Yanxia Hu (Food and Chemical Toxicology, 2026)

Mechanistic insights into Pb2+-mediated benzohydroxamic acid adsorption and bubble attachment on rutile - Di Meng; Yongxiang Sun; Bin Yan; Rong Yang; Wenjihao Hu; Hongbo Zeng (Chemical Engineering Journal, 2026)

Molecular rivet-enhanced in situ polymerized nonconventional luminescent hydrogels for rapid and sensitive biosensing - Xin Gao; Tao Zeng; Caixia Pei; Ruiwei Hu; Rong Hu; Tiantian Yang; Zhanglin Liu; Wei Cheng; Fengjiao Chen (Analytica Chimica Acta, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Divergent responses of ecosystem water use efficiency to environmental drivers in arid versus humid regions - Hailing Li; Maohong Wei; Hongling Yang; Ya Hu; Shaokun Wang; Ping Yue; Xujun Ma; Fangwei Hao; Rong Ma; Xiaoan Zuo (Journal of Environmental Management, 2026)

Screening of ACE inhibitory peptides in digestive products of TGase-induced GCSG and evaluation of their absorption and transport properties - Chenghong Jiang; Mingrong Chen; Qilin Huang; Youming Liu; Jianhua Rong; Mingtao Yang; Xibo Wang; Yang Hu (Food Chemistry, 2026)

A decomposition-based reinforcement learning approach for production and distribution integrated scheduling problem of perishable products - Yuan-yuan Yang; Bin Qian; Li-jun Wang; Jun-qing Li; Rong Hu (Swarm and Evolutionary Computation, 2026)

Retraction notice to “Gravity-driven high flux filtration behavior and microbial community of an integrated granular activated carbon and dynamic membrane bioreactor for domestic wastewater treatment” [Sci. Total Environ. 825 (2022) 53930] - Yuan Yang; Weihang Deng; Yisong Hu; Rong Chen; Xiaochang C. Wang (Science of The Total Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

NPFF2 regulate thiamethoxam resistance by over-expressing CYP6CX4 in Bemisia tabaci - Ying Zhang; Rong Zhang; Hantang Lu; Buli Fu; Xiaojie Wu; Hu Xue; Xuegao Wei; Youjun Zhang; Xin Yang (Pesticide Biochemistry and Physiology, 2026)

Biodegradable plastic mulches: Distinct effects on microbial communities but no impact on soil multifunctionality during cabbage production - Rong Liang; Lei Mei; Jina Ding; Li Wang; Mouliang Xiao; Yongfu Li; Xiao Liu; Changlong Shao; David R. Chadwick; Davey Jones; Fan Ding; Can Hu; et al. (Journal of Hazardous Materials, 2026)

Acquisitive, diverse tree stands resist vine invasion via contrasting temporal effects on crown volume and herb cover - Li Zhang; Liting Zheng; Marc W. Cadotte; Charles A. Nock; Baiyu Yang; Zhiming Hu; Ciliang Zhao; Wen-Hui You; En-Rong Yan (Forest Ecology and Management, 2026)

Divergent controls on particulate and mineral-associated organic carbon in tropical forests of southern China - Dong Qiao; Licong Dai; Meihua Yang; Yue Jiao; Qiaoyan Chen; Rong Shang; Zhongmin Hu (Plant and Soil, 2026)

Bioavailability, Migration, and Accumulation Characteristics of Heavy Metals in the Soil–Lotus Root System Adjacent to Highways - Qiang Hu; Rong-hua Qiu; Ren-chao Zhu; Manisha Parajuli; Si-jie Wen; Zi-yang Sun; Ai-hua Yu (International Journal of Environmental Research, 2026)

Research progress on the fermentation characterization of non- Saccharomyces yeasts in fruit wines: a review - Rong Zhang; Xiaoyan Hou; Qigao Fan; Kaidi Hu; Lunqiong Hou; Ning Kang; Ziyuan Ou; Ning Zhao; Qin Li; Aiping Liu; Yong Yang; Guoquan Han; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Isolation, identification, and disease-protective potential of Pseudomonas monsensis DBFF02 against Saprolegnia infection in grass carp - Guofan Zhang; Kunyan Li; Yuyuan Peng; Simei He; Chen Li; Rong Fan; Jiajie Xie; Linger Qian; Xinran Long; Jiayi Wang; Jiatao Yang; Yanmin He; et al. (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Ion-specific multiscale regulation of gelatinization and retrogradation in normal and waxy wheat starches: Cooperative roles of valence, hydration, and molecular chain architecture - Tian Lv; Xin-rong Lv; Shu-ning Yuan; Yu Hu; Rong-ran Zhang; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Proanthocyanidin/laccase-mediated cross-linking enhances the structural stability and rheological properties of collagen solutions - Junhong Xie; Li Feng; Fanghui Deng; Wei Yue; Wei Liang; Qiannan Zhao; Wentao Ma; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2026)

An octahedral CeO2 artificial interphase for dendrite-free and stable zinc-ion supercapacitors - Zhan Yang; Rong Liao; Sunwu Hu; Weiming Chen; Deliang Zeng; Zhuoyu Ji; Jia Hong Pan; Xiaolei Huang (Chemical Engineering Journal, 2026)

Improving spatial resolutions of unmanned aerial vehicle hyperspectral images to predict grain yield and protein content in rice - Zhonglin Wang; Rong Hu; Mingming Hu; Huilai Yin; Tao Liu; Yufei Xie; Yangming Ma; Feng Yang; Feijie Li; Zhiyuan Yang; Yongjian Sun; Jun Ma (Precision Agriculture, 2026)

Genome-wide Identification and Expression Analysis of the ABF Gene Family in Achnatherum splendens - Shan Yin; Mingsu Chen; Ming Hu; XiaoYing Li; Jingru Wang; Jiahuan Niu; Zhangqi Song; Huan Yang; Hongbing Li; Rong Li (Plant Molecular Biology Reporter, 2026)

CRISPR/Cas12a-mediated electrochemiluminescent biosensor integrating Ag modified Co-doped metal-organic frameworks for dual detection of malathion and phorate - Ying Zhang; Wenke Liu; Rong Guo; Yanli Qi; Baoqing Bai; Jinhua Zhang; Nan Hu; Ying Gu; Yukun Yang; Shuo Wang (Analytica Chimica Acta, 2026)

Brain gray matter atrophy in adult population with cognitive impairment due to chronic cadmium exposure - Zhentao Gao; Longtao Yang; Rong Ma; Xiaoying Li; Fang Pei; Wei Hu; Yixuan Wu; Xiaojiang Tang; Jun Liu (NeuroToxicology, 2026)

Numerical simulation of fracture propagation and interwell frac-hit mechanism in deep shale gas infill wells - Yufeng Wang; Qiang Wang; Jinzhou Zhao; Yongquan Hu; Jianglong Wang; Juhui Zhu; Rong Wang; Xiaowei Li; Yu Yang (Engineering Geology, 2026)

Morphology and ultrastructure of the proventriculus in the mole cricket Gryllotalpa orientalis Burmeister, 1838 (Orthoptera: Gryllotalpidae) - Bai-Long Yang; Ling Zhu; Ya-Rong Gu; Huan Hu; Ying Miao (Arthropod Structure & Development, 2026)

Genetic basis of pedicellate spikelet masculinization in maize revealed by an advanced maize–teosinte population - Ruifan Bao; Xueying Wang; Junle Wu; Ting Liang; Xiya Hu; Pengxu Meng; Hang Mi; Peng Li; Sijia Yang; Zhiqin Liu; Siyu Lei; Jinyu Yang; et al. (Planta, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Spatiotemporal patterns and driving mechanisms of net primary productivity along urban-rural gradient in Xi’an, China - Nafang Zhou; Tianhao Bai; Rong Hu; Enjun Gong; Yang Zhang; Yang Liu; Jun Wang (Urban Forestry & Urban Greening, 2026)

Immunogenicity and safety of an Escherichia coli-produced 9-valent HPV vaccine in adolescents aged 9 to 17 compared with young women - Yulin Jing; Xiaowen Hu; Li Zhang; Jiangyahui Wang; Fei Yang; Rong Wang; Ying Jiang; Lingling Nie; Zhongqiang Jin; Xuecheng Liu; Sihai Li; Chao Du; et al. (Science Bulletin, 2026)

Fe2O3/SiC oxygen carrier for enhanced syngas production via microwave-assisted chemical looping gasification of municipal sewage sludge - Panbo Yang; Jiatao Dang; Xiaoyu Yan; Lianchao Xu; Shuheng Zhao; Sian Wu; Hangyu Yan; Wei Wang; Haojie Rong; Kaixin Wang; Jianjun Hu (Chemical Engineering Journal, 2026)

Long-term wheat field fertilization shapes soil microbial antibiotic resistance genes through bacterial community modulation on the Loess Plateau - Mengmeng Wen; Rong Hu; Jinfa Chen; Caidi Yang; Jun Wang; Yang Liu (Plant and Soil, 2026)

Extreme drought decouples nematode diversity from soil function in grassland ecosystems, Northern China - Zonghao Hu; Shuang Pang; Sixue Chen; Rong Hao; Meixia Liu; Rong Mao; Yang Zhang; Anton A. Goncharov; Ximei Zhang (Applied Soil Ecology, 2026)

Study on diagnosis of subclinical mastitis and identification of pathogens using electronic nose detection of cow’s milk - Fang Wang; Yujun Zhu; Enqiu Zhang; Rong Zhang; Hongwei Duan; Shuai Yang; Xianghong Du; Xingxu Zhao; Xiaofei Ma; Lihong Zhang; Junjie Hu (Computers and Electronics in Agriculture, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Upcycling anaerobic digestion methane to single-cell protein as a low-carbon strategy - Pan-Long Lv; Qing-Rui Hu; Yu-Yang Hu; Wenjing Gong; Qian Li; Rong Chen (Resources, Conservation and Recycling, 2026)

The role of heterogeneity in groundwater chemistry and mixing within the critical zone of a volcanic rock hillslope - Tao Yang; Jiu Jimmy Jiao; Rong Mao; Xin Luo; Jeffrey Wong; Jinchao Zuo; Wenli Hu; Jiawei Liang; Yanqiong Huang; Xiaoyan Shi (Journal of Hydrology, 2026)

One stone, two birds: Preparation of nutritionally fortified and easy-to-swallow 3D printed pea protein gel based on high internal phase emulsions - Wei Liang; Junhong Xie; Qiannan Zhao; Chenghong Jiang; Xiaofeng Zhan; Mingrong Chen; Lu Zhang; Chuan Li; Jianhua Rong; Yang Hu (Food Hydrocolloids, 2026)

Phosphate-modified attapulgite for efficient Pb(II) and Cd(II) removal: surface functionalization and adsorption mechanisms - Xinyao Zhang; Rong Yang; Wenxia Zhu; Di Meng; Xuanjie Huang; Zulin Wang; Bo Ma; Jun Yao; Wenjihao Hu (Environmental Research, 2026)

Longifolene and β-ionone promote astaxanthin accumulation in Microcystis aeruginosa by serving signaling function - Lexin Huang; Fei Jiang; Shanshan Song; Xinyuan Zhao; Zhehan Yang; Junjie Ma; Haozhe Xu; Rong Hu; Tianyu Huang; Zhijie Chen; Huiying Fu; Zhaojiang Zuo (Algal Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Overlooked role of soil microbial-derived carbon in promoting neurotoxic methylmercury production - Man Yang; Zhi-Cheng Hu; Hui-Wen Liu; Wen Zhang; Yun-Yun Hao; Qin Liu; Jia-Xuan Meng; Bo Meng; Qiaoyun Huang; Baohua Gu; Yu-Rong Liu (Journal of Hazardous Materials, 2026)

A novel strategy for controlling nitrite accumulation in fermented cabbage by regulating microbial community structure via cold plasma - Lin Zhu; Mengke Cheng; Yuan Wang; Xinyu Hu; Rong Wang; Biyue Yang; Xiang Xiao; Wei Wei (Food Control, 2026)

Increasing aridity reduces soil protist diversity and weakens its link to ecosystem functioning in grassland ecosystem, northern China - Rong Hao; Shuang Pang; Zonghao Hu; Wei Yang; Ximei Zhang; Haiyan Ren (Soil Ecology Letters, 2026)

Organic fertilization improves activities of phosphomonoesters hydrolase in rhizosphere to facilitate phosphorus acquisition in cucumber and accumulates organic phosphorus in soil - Bingshuang Wang; Yuan Wang; Xihe Zhang; Xiaodan Hu; Shujun Li; Yifei Sun; Yang Wang; Yan Sun; Ziwei Dai; Yunsheng Lou; Rong Li; Guohua Xu; et al. (Applied Soil Ecology, 2026)

Coordinated horizontal transfer of multiple genes assembles a carotenoid biosynthesis pathway in aphids - Rong Hu; Jun Wu; Siying Li; Peiyu Yang; Gang Wu; Changying Niu; Shuai Zhan; Yazhou Chen (Insect Biochemistry and Molecular Biology, 2026)

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

Neonicotinoids and human health: Environmental fate, toxicity mechanisms, and future directions - Kangming Ji; Yu Rong; Zihang Zhang; Yunjie Chen; Ruixin Hu; Yuchen Chu; Yuyi Tang; Lijun Qian; Chuang Yang (Pesticide Biochemistry and Physiology, 2025)

Electronic structure engineering of Fe/Co dual-atom catalysts enhances ultrafast Fenton-like reactions mediated by high-valent iron-oxygen-cobalt bridged complexes for safe pollutant removal - Huan Cheng; Peng Wei; Mingjia Liu; Yunhui Yang; Long Huang; Jian Tang; Rong Hu (Journal of Hazardous Materials, 2025)

Simulated analog crayfish meat based on 3D print: Effect of crayfish oil emulsion on gel properties of surimi - Xiaofeng Zhan; Shuhui Yang; Weixia Zhou; Yanyan Wang; Jianhua Rong; Youming Liu; Chuan Li; Yongqiang Zhao; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Single nucleotide variations triggered responsive strip for Helicobacter pylori theranostics - Lin-Min Zhong; Qi-Ling Yang; Xin-Yi Zhong; Xiao-Rong Zhang; Fen-Ying Kong; Shan-Wen Hu; Ai-Lin Liu (Chemical Engineering Journal, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Unraveling the role of pyridyl sites in UiO-67 type MOFs supported Pd NPs for boosting formic acid dehydrogenation - Jiewei Rong; Rongmei Zhang; Mai Xu; Xu Chen; Xinyue Yang; Jinsong Hu; Xiru Cao; Zhentao Liu; Chunming Xu; Chunhui Zhou; Xilong Wang (Chemical Engineering Journal, 2025)

High-Resolution Three-Pressure Prediction of Lianggaoshan Formation in LT1 Well block of Eastern Sichuan Risk Exploration Area - Yu-wei Wang; Ke-zhen Wan; Rong-rong Zhao; Wen-hao Li; Yang Lin; Hao Long; Hu Zhao (Applied Geophysics, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Effects of EGCG/TGase on the physicochemical properties and in vitro dynamic digestion characteristics of water-saving rinsed surimi gels - Qin Yang; Weixia Zhou; Die Hu; Chuan Li; Lu Zhang; Yongqiang Zhao; Shengbi Zou; Ru Liu; Youming Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Insights into the synergistic cross-linking effect of EGCG and TGase on surimi gels - Qin Yang; Jinling Li; Wentao Ma; Ru Liu; Shengbi Zou; Yongqiang Zhao; Shanbai Xiong; Jianhua Rong; Yang Hu (Food Chemistry, 2025)

Sustainable bipolar membranes with three-dimensional flower-like spherical MgAl-layered double hydroxides doped quaternized chitosan for accelerated water dissociation and durability - Ming Li; Jinyun Xu; Hongze Li; Xiaoqing Wang; Shijie Shang; Xiaoyan Wang; Sijia He; Yanyan Ji; Li Yang; Rong Kuang; Chenxin Hu; Wenju Zhu; et al. (Desalination, 2025)

Electrochemical exfoliation of poly(triazine imide)-coated graphene oxide for the in-situ synthesis of composite proton exchange membranes with enriched phosphoric acid channels - Qingting Liu; Ying Zhou; Bei Wang; Zhiwei Ling; Xudong Fu; Rong Zhang; Shengfei Hu; Gang Xiao; Xiao Li; Feng Zhao; Jun Yang (Chemical Engineering Journal, 2025)

A durable immuno-protective core-shell microgel for the enhanced pancreatic islet transplantation in diabetes therapy - Zeming Hu; Yang Luo; Muhammad Junaid; Rong Xu; Yaoqi Chen; Jie Yao; Renhao Ni; Tong Zhu; Hua Zhang; Huiqing Ding; Yabin Zhu (Chemical Engineering Journal, 2025)

Confined Ostwald ripening approach towards highly durable and flexible 3D PTFE aerogels boosting Pickering emulsion separation in bi-phase photocatalysis - Yuxin Zhang; Jiawei Huangfu; Bin Rong; Xiongfei Du; Yang Hu; Xu Zeng; Kaikai Chen; Changkun Ding; Wenping Hu; Kuo Yuan; Qinglin Huang (Chemical Engineering Journal, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Chemically gated ion transport in two-dimensional heterogeneous membranes with ultrahigh metal ion selectivity - Gang Yuan; Junjie Fang; Yukun Sun; Jiaojiao Ma; Hao Wang; Wanqi Zhou; Yu Jiang; Chongyang Yang; Zhihua Zhou; Rong Hu; Mingyang Xia; Konstantin S. Novoselov; et al. (Science Bulletin, 2025)

Photochemical oxidation mechanisms and toxicity evolution of photostable atrazine during sunlight/free chlorine process - Xiaoyan Y. Ma; Xiaoru Li; Haixiang Jia; Jiahui Kho; Jiangyong Hu; Shengjiong Yang; Rong Chen; Xiaochang C. Wang; Nan Wang (Journal of Environmental Chemical Engineering, 2025)

Analysis of starch structure, functional properties, and the underlying molecular mechanism in SeaRice86 (SR86) - Yongxiang Huang; Xiao Yang; Yilan Cui; Mangu Hu; Yunliang Rong; Yu Ling; Rongchao Yang; Yueqin Zhang (Carbohydrate Polymers, 2025)

Research on quantitative monitoring of new meteorological-agricultural compound drought characteristics - Yang Yu; Lei Zhou; Wenliang Wang; Rong Tian; Jingxin Zhang; Senmiao Hu; Qingzhu Zhang; Yalan Li (Theoretical and Applied Climatology, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Epidemiological characteristics and clinical treatment of melioidosis: a 11-year retrospective cohort study in Hainan - Tianzhou Lan; Guangqiang Zhao; Haichao Liu; Lei Qu; Qingjia Chi; Beibei Meng; Juan Fang; Fang Yang; Zhenhong Hu; Bin Wang; Rong Lin; Chenlong Rao; et al. (Infectious Diseases, 2025)

Similarity analysis and verification of the relationship between resistance coefficients in porous media of different scales: Focusing on slatted floor - Qizhi Yang; Li Rong; Yao Tao; Jiyuan Tu; Jinyong Wang; Xi Bai; Zhiru Hu; Jie Chai; Yong Wang; Guoqiang Zhang (Biosystems Engineering, 2025)

H3K18 lactylation drives the progression of silica nanoparticles-induced pulmonary fibrosis via promoting macrophage M1 polarization - Lili Shi; Lin Zhang; Zhenfang Ma; Zhaohui Hu; Zihan Geng; Hao Liu; Jingyuan Wang; Ke Feng; Yiheng Geng; Yan Liu; Cunhui Zhang; Yujia Xie; et al. (Journal of Hazardous Materials, 2025)

Donor-receptor coordination mediated multiple antigens capture and transport for augmented cancer immunotherapy - Huan Liang; Qingqing Lu; Runyu Hu; Yixiao Zhang; Xing Rong; Guocan Yu; Jie Yang (Chemical Engineering Journal, 2025)

Intrinsic nanoconfinement design in halloysite nanotubes enhances the affinity of zirconium phosphate for efficient removal of heavy metal ions - Rong Yang; Di Meng; Xinyao Zhang; Weixuan Zhao; Xuanjie Huang; Zulin Wang; Bo Ma; Jun Yao; Wenjihao Hu (Chemical Engineering Journal, 2025)

Protein/polysaccharide composite nanocoating based on amyloid-like aggregation for fresh-cut fruits preservation - Guichen Liu; Rong Liu; Chengyu Fu; Xiang Hu; Ke Li; Luke Yan; Peng Yang; Jian Zhao (Chemical Engineering Journal, 2025)

Atrazine exposure induces TDP-43 protein translocation: A potential mechanism for prefrontal cortical neurodegeneration induced by environmental pollutants - Yuan Ma; Kaidong Wang; Yuxuan Jiao; Yujing Li; Rong Hu; Yang Li; Ge Shi; Min Huang (Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Electro-conductive nylon mesh assisted electro-chemical membrane bioreactor process (EMBR) for municipal wastewater treatment - Songhua Li; Yisong Hu; Jinzhuo Shi; Wenqian Xiao; Yuan Yang; Rong Chen (Journal of Water Process Engineering, 2025)

Metal exposure is associated with cognitive function and plasma sTrem2 levels in coal miners: a cross-sectional study - Yang Li; Kaidong Wang; Ge Shi; Ai Qi; Yujing Li; Yuxuan Jiao; Rong Hu; Guilin Hu; Yonghang Li; Zhuoheng Shen; Min Huang (Environmental Research, 2025)

Deep reinforcement learning algorithm incorporating problem characteristics for dynamic multi-objective permutation flow-shop scheduling problem - Yuan-Yuan Yang; Bin Qian; Rong Hu; Zuocheng Li; Zi-Qi Zhang; Huai-Ping Jin; Jian-Bo Yang (Swarm and Evolutionary Computation, 2025)

Relationships between soil health and dynamics of soil potential pathogenic microbiota in functional domains of Xi'an urban greenspaces, China - Yang Liu; Mengya Kou; Rong Hu; Fazhu Zhao; Jun Wang (Environmental Research, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Corrigendum to “Stable isotope tracing reveals glucose metabolism characteristics of drug-resistant B-cell acute lymphoblastic leukemia” [Analytica Chimica Acta 1352 (2025) 343884] - Rong Hu; Zhengwei Duan; Mengyao Wang; Mengting Liu; Yaoxin Zhang; Yanxi Lu; Yuhan Qian; Enjie Wei; Jianghua Feng; Pengfei Guo; Yang Chen (Analytica Chimica Acta, 2025)

Structural evaluation and formation regularities of garlic clove-like meat in prefabricated grass carp - Qin Yang; Junhong Xie; Yuting Zhang; Yiling Tian; Liang Song; Yongqiang Zhao; Jian Xiong; Ru Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Insights into Leuconostoc-clade as starters in Chinese paocai: Shaping microbial communities for rapid, safe, and flavor-preserving fermentation - Xinyu Hu; Mengke Cheng; Meng Zhang; Biyue Yang; Rong Wang; Juan Bai; Jiayan Zhang; Wei Wei; Lin Zhu; Xiang Xiao (Food Bioscience, 2025)

Asymbiotic Nitrogen Fixation in the Phyllosphere of Urban Green Spaces - Jian-Feng Li; Le-Yang Yang; Zhao Zhang; Xin-Rong Huang; Hu Li; Shun Li; Xiao-Ru Yang (Current Microbiology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Recent progress in protein-based high internal-phase Pickering emulsions: Composition, stabilization, applications, and future trends - Wei Liang; Xiaofeng Zhan; Pengkai Wang; Chuan Li; Lu Zhang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Stable isotope tracing reveals glucose metabolism characteristics of drug-resistant B-cell acute lymphoblastic leukemia - Rong Hu; Zhengwei Duan; Mengyao Wang; Mengting Liu; Yaoxin Zhang; Yanxi Lu; Yuhan Qian; Enjie Wei; Jianghua Feng; Pengfei Guo; Yang Chen (Analytica Chimica Acta, 2025)

Dual-mode sensing platform based on an iodide ion synergistic covalent triazine frameworks (CTFs) for point-of-care testing (POCT) of acetylcholinesterase - Yanyue Chen; Huan Cheng; Hongling Tao; Jiali Liu; Yulong Li; Qiu-Xia Li; Tong Yang; Shuang Meng; Yunhui Yang; Rong Hu (Analytica Chimica Acta, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

The promotional effect of MoO3 on the CeO2/TiO2 catalyst for simultaneous removal of NO and toluene: From the insights of experimental and DFT studies - Zhuang Hu; Yi-fei Yu; Hai-yuan Zhao; Zheng-long Wu; Rong Guo; Jia-le Zhou; Xin-yue Zhou; Bing Zhang; Yang-wen Wu; Li Zhao; Qiang Lu (Journal of Environmental Chemical Engineering, 2025)

Comparative analysis of three extraction methods for ginger leaf polysaccharide: Chemical composition, antioxidant activity, and hypolipidemic effects - Zhong-hao Zhang; Zhong-hua Zhao; Tian-yi Cao; Cai-rong Yang; Zi-zhong Tang; Shi-ling Feng; Shu Yuan; Sheng-lin Hu; Ming Yuan (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Single-cell atlas profiling revealed cellular characteristics and dynamic changes after PD-1 blockade therapy of brain metastases from laryngeal squamous cell carcinoma - Yunzhi Zou; Hao Duan; Zekun Deng; Rong Xiang; Jixiang Zhao; Zhenhua Zhang; Wanming Hu; Yuanzhong Yang; Zeming Yan; Shujuan Wen; Zexian Liu; Gao Zhang; et al. (Molecular and Cellular Biochemistry, 2025)
Brain metastasis (BM) in laryngeal squamous cell carcinoma (LSCC) is uncommon but prognosis is poor. Anti-PD-1 immunotherapy benefits some advanced LSCC cases, yet its efficiency is limited by tumor complexity. We analyzed paired metastatic tumor samples from before and after immunotherapy using single-cell RNA sequencing (scRNA-seq), along with a primary LSCC dataset and bulk RNA sequencing. This identified changes post-immunotherapy and revealed differences in single-cell transcriptomes among LSCC, primBM, and neoBM. Our findings show that anti-PD-1 treatment suppresses metastasis-promoting pathways like VEGF and EMT in cancer cells, and alters immune cell functions. Notably, it upregulates T cell activation, leading to CD8 T cell exhaustion from excess heat shock proteins, notably HSPA8. However, CD8 T cell cytotoxic functions improve post-treatment. In myeloid cells, anti-PD-1 therapy enhances antigen presentation and promotes a proinflammatory shift post-metastasis. Additionally, NUPR1 is linked to BM in LSCC, and NEAT1 is a potential metastatic cancer cell cycle participant. Our study provides insights into cancer heterogeneity and the impact of PD-1 immunotherapy on metastasis, aiding precise diagnosis and prognosis.

Cytochrome P450 CYP6EM1 confers resistance to thiamethoxam in the whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) via detoxification metabolism - Mingjiao Huang; Peipan Gong; Cheng Yin; Jing Yang; Shaonan Liu; Buli Fu; Xuegao Wei; Jinjin Liang; Hu Xue; Chao He; Tianhua Du; Chao Wang; et al. (Pesticide Biochemistry and Physiology, 2025)

Petrogenesis and geodynamic implications of gabbroic diorites of the early Paleozoic Mijiashan ophiolite in the eastern North Qilian Orogenic Belt, NW China - Jiao-Long Zhao; Liang Liu; Qing-Yan Tang; Jin-Rong Wang; Zhen-Xi Yang; Pei-Qing Hu; Xin-Wei Zhai; Saniye Abdereyimu; Zi-Han Dang (Journal of Asian Earth Sciences, 2025)

Inhibition regulatory mechanism in Staphylococcus aureus under cold plasma oxidative stress - Rong Du; Xiao Yang; Jun-Hu Cheng (Food Bioscience, 2025)

Toxic aldehydes in fried foods: Formation, analysis, and reduction strategies - Xing-yang Guo; Liang-yu Cheng; Chao Chang; Xiao-ming Jiang; Pan Gao; Wu Zhong; Chuan-rong Hu; Dong-ping He; Jiao-jiao Yin (Food Control, 2025)

Research on Optimization Method for Irregular Seismic Acquisition in Curved Wave Domain Based on Simulated Annealing - Hu Zhao; Meng-yang Chen; Yu-dong Ni; Rong-rong Zhao; Fu-hao Jiang; Wei Chen; Jing-yun Dai (Applied Geophysics, 2025)

Airborne Investigation of Riming: Cloud and Precipitation Microphysics within a Weak Convective System in North China - Xiangfeng Hu; Hao Huang; Shaoyu Hou; Kun Zhao; Chuanfeng Zhao; Yinghui Lu; Jiefang Yang; Rong Zhang; Delong Zhao; Weiguo Liu; Dan Zhang; Haixia Xiao (Advances in Atmospheric Sciences, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Contribution of phosphorylation modification by sodium tripolyphosphate to the functional properties of hollow zein nanoparticles - Sheng-qi Rao; Cao-chen Jia; Lin Du; Wei-biao Zhou; Wen-xuan Hu; Yi Jiang; Zhi-rong Wang; Zhen-quan Yang (Food Research International, 2025)

Smartphone-based dual-mode aptasensor with bifunctional metal-organic frameworks as signal probes for ochratoxin A detection - Yu-Long Li; Yan-Yue Chen; Fa-Ting Xie; Qiu-Xia Li; Tong Yang; Yun-Hui Yang; Rong Hu (Food Chemistry, 2025)

Nickel-iron layered double hydroxide and CoMoO4 composites supported on nickel foam as efficient bifunctional catalyst for water electrolysis - Xin Xiao; Rao Ma; Ke Jiang; Lushan Ma; Qiyao Wang; Shuang Meng; Tong Yang; Zhuo Qiu; Rong Hu; Long Huang (Fuel, 2025)

Ternary Ni:Fe- activated inert Cu-based electrocatalyst as efficient bifunctional electrocatalysts for water splitting - Shi-Yu Lu; Chunjie Wu; Tingting Hu; Ling Wang; Wenzhao Dou; Jun Zhang; Rong Wang; Yin Liu; Qian Yang; Zhigang Zou; Meng Jin (Chemical Engineering Journal, 2025)

Scaled experimental study of a ventilation system featuring partition jet and pit exhaust - Qizhi Yang; Xi Bai; Guoqiang Zhang; Li Rong; Yao Tao; Jiyuan Tu; Jinyong Wang; Zhiru Hu; Jie Chai; Yong Wang (Biosystems Engineering, 2024)

Prevalence and genetic characterization of linezolid resistance gene reservoirs in hospital sewage from Zhejiang Province, China - Weiyi Shen; Yanyan Hu; Dejun Liu; Yang Wang; Stefan Schwarz; Rong Zhang; Jiachang Cai (Science of The Total Environment, 2024)

Integrative transcriptomic analysis reveals a broad range of toxic effects of triclosan on coral Porites lutea - Hao Liang; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Rong-Gui Zhu; Chao-Yang Zhou; Zhen-Zhu Liu; Kefu Yu (Journal of Hazardous Materials, 2024)

Strong electronic interaction in chromium-molybdenum dual incorporated few-layer cobalt sulfide nanosheets with lattice distortion for efficient bifunctional water splitting - Shi-Yu Lu; Wenzhao Dou; Chunjie Wu; Jun Zhang; Ling Wang; Tingting Hu; Rong Wang; Yin Liu; Qian Yang; Meng Jin (Fuel, 2024)

The effect of mixed microbial agents on tobacco black shank disease - Fang Liang; Chai Yunxia; Li Yuanyuan; Geng Shaowu; Bu Yunhong; Hu Yang; Ai Kebiao; Shi Jianfei; Duan Jiyou; Yang Maosong; Zhu Rong (Physiological and Molecular Plant Pathology, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Regulation of wheat yield by soil multifunctionality and metagenomic-based microbial degradation potentials under crop rotations - Yang Liu; Mengmeng Wen; Rong Hu; Fazhu Zhao; Jun Wang (Journal of Environmental Management, 2024)

Combined utilization of slag, fly ash, and polyacrylamide for sustainable saline soil improvement: a win-win strategy - Yang Zhao; Zheng Lu; Rong Zhang; Jie Liu; Changtao Hu; Abdollah Tabaroei; Jian Li; Tingzhou Yan; Hailin Yao (Bulletin of Engineering Geology and the Environment, 2024)

A potential trade-off between reproduction and enhancement of thermotolerance in Liriomyza trifolii populations driven by thermal acclimation - Yu-Cheng Wang; Ya-Wen Chang; Fei Yang; Wei-Rong Gong; Jie Hu; Yu-Zhou Du (Journal of Thermal Biology, 2024)

A review of electro-conductive membrane enabled electrochemical anaerobic membrane bioreactor process for low-carbon wastewater treatment - Yisong Hu; Jiashun Wang; Jinzhuo Shi; Yuan Yang; Jiayuan Ji; Rong Chen (Journal of Environmental Chemical Engineering, 2024)

Development of easy-to-swallow and lipid-enhanced 3D printed surimi based on high internal phase emulsions - Wei Liang; Yuhang Wang; Chuan Li; Pengkai Wang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

City-level resilience assessment of integrated energy systems in China - Jingna Yang; Kaile Zhou; Rong Hu (Energy Policy, 2024)

Enhanced antifouling behavior and phosphorus removal in a gravity-driven electrochemical dynamic membrane bioreactor (EDMBR) process: Performance and mechanisms - Yisong Hu; Lulu Zha; Luhe Tang; Jingyu Zhang; Weihang Deng; Yuan Yang; Zhenzhen Yu; Rong Chen (Chemical Engineering Journal, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Ca2+-nano starch-lutein endowed 3D printed surimi with antioxidation and mutual reinforcing transmembrane transport mechanisms via hepg2 and caco-2 cells model - Gaoshang Li; Rong Shi; Junqi Zhan; Yiduo Wu; Yue Wan; Qian Yao; Yaqin Hu; Chunhua Wu; Wenge Yang; Wubo Wan (Food Research International, 2024)

Preparation, characterization, and coating effect of bio-active nano-emulsion based on combined plant essential oils on quality of grass carp fillets - Mingtao Yang; Yunshan Zhu; Tianhao Ying; Jianhua Rong; Pengkai Wang; Yang Hu (Food Chemistry, 2024)

Synthesis and application of gelatin-based controlled-release antibacterial films containing oregano essential oil/β-cyclodextrin microcapsules for chilling preservation of grass carp fillets - Tianhao Ying; Chenghong Jiang; Sadia Munir; Ru Liu; Tao Yin; Juan You; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2024)

Rapid adsorptive removal of emerging and legacy per- and polyfluoroalkyl substances (PFASs) from water using zinc chloride-modified litchi seed-derived biochar - Zhen-Zhu Liu; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Hong-Ming Tan; Rong-Gui Zhu; Chao-Yang Zhou; Hao Liang; Kefu Yu (Bioresource Technology, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

Integrated assessment of bioaerosol dispersion patterns and infection risk in a typical urban environment: Implications for urban biosecurity management - Zhijian Dong; Zhijian Liu; Chenxing Hu; Xuqiang Shao; Haokang Yang; Yongjun Jin; Rui Rong (Sustainable Cities and Society, 2024)

Digestion and absorption characteristics of iron-chelating silver carp scale collagen peptide and insights into their chelation mechanism - Qiannan Zhao; Wei Liang; Zhe Xiong; Chuan Li; Lu Zhang; Jianhua Rong; Shanbai Xiong; Ru Liu; Juan You; Tao Yin; Yang Hu (Food Research International, 2024)

An approach based on a combination of toxicological experiments and in silico predictions to investigate the adverse outcome pathway (AOP) of paraquat neuro-immunotoxicity - Chunhui Zhang; Ge Shi; Qi Meng; Rong Hu; Yang Li; Guiling Hu; Kaidong Wang; Min Huang (Journal of Hazardous Materials, 2024)

Management of resilient urban integrated energy system: State-of-the-art and future directions - Rong Hu; Kaile Zhou; Jingna Yang; Hui Yin (Journal of Environmental Management, 2024)

Simultaneous determination of trace marine lipophilic and hydrophilic phycotoxins in various environmental and biota matrices - Chao-Yang Zhou; Chang-Gui Pan; Feng-Jiao Peng; Rong-Gui Zhu; Jun-Jie Hu; Kefu Yu (Marine Pollution Bulletin, 2024)

Human milk oligosaccharide 2′-fucosyllactose alleviates DSS-induced ulcerative colitis via improving intestinal barrier function and regulating gut microbiota - Xianxiang Chen; Jiaruo Hu; Jun Yang; Qiang Yu; Yi Chen; Mingyue Shen; Liyuan Rong; Jianhua Xie (Food Bioscience, 2024)

Effects of Hericium erinaceus polysaccharide in porcine IPEC-J2 intestinal epithelial cells against apoptosis induced by oxidative stress - Jian Li; Jia-rong Mo; Shi-yu Hu; Xin Dong; Jia-wei Li; Li-yu Yang; Yi-jian Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Glutathione S-transferase directly metabolizes imidacloprid in the whitefly, Bemisia tabaci - Rong Zhang; Jing Yang; Jinyu Hu; Fengbo Yang; Jinjin Liang; Hu Xue; Xuegao Wei; Buli Fu; Mingjiao Huang; He Du; Chao Wang; Qi Su; et al. (Pesticide Biochemistry and Physiology, 2024)

Radio frequency heating induced 3D printed white croaker (Argyrosomus argentatus) surimi gelation: Effectiveness and gel quality evaluation - Yaxing Yang; Feifan Cao; Rong Han; Feng Li; Hu Shi; Fanbin Kong; Yang Jiao (Innovative Food Science & Emerging Technologies, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

Advances in ionogels for proton-exchange membranes - Yilin Zhou; Bei Wang; Zhiwei Ling; Qingting Liu; Xudong Fu; Yanhua Zhang; Rong Zhang; Shengfei Hu; Feng Zhao; Xiao Li; Xujin Bao; Jun Yang (Science of The Total Environment, 2024)

Regulation of wheat growth by soil multifunctionality and metagenomic-based microbial functional profiles under mulching treatments - Yang Liu; Rui Liu; Zhen Feng; Rong Hu; Fazhu Zhao; Jun Wang (Science of The Total Environment, 2024)

Comparative analysis of process selection and carbon emissions assessment of innovative steelmaking routes - Botao Xue; Guangsheng Wei; Yanze Hou; Hang Hu; HongJin Zhang; Rong Zhu; Kai Dong; Chao Feng; Lingzhi Yang; Hongbin Wang (Journal of Cleaner Production, 2024)

Electrospinning-assisted construction of rapid proton conduction channels in halloysite nanotube-encapsulated ionic liquid-embedded sulfonated poly(ether ether ketone) proton exchange membranes - Chunyong Xiong; Zhiwei Ling; Bei Wang; Yang Yu; Qingting Liu; Xudong Fu; Chonggang Wu; Rong Zhang; Shengfei Hu; Xujin Bao; Jun Yang (Fuel, 2024)

Interfacial behavior and micro-rheological performance of Pickering emulsions co-stabilized by β-cyclodextrin and xanthan gum - Wei Liang; Fanghui Deng; Yuhang Wang; Wei Yue; Die Hu; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Three-dimensional DNA biomimetic networks (B-3D Net)-based ratiometric fluorescence platform for cancer-related gene biosensing - Chao Yao; Guiqun Zhang; Hongling Tao; Yulong Li; Rong Hu; Yunhui Yang (Analytica Chimica Acta, 2024)

Photo-driven dynamic hydrogel modulates bone marrow mesenchymal stem cells behavior for enhanced cartilage regeneration - Wenjie Zhang; Wenliang Xue; Zhaoli Jia; Rong Yang; Penghui Wang; Yi Hu; Xiaoyan Tan; Qiang Chen; Bo Chi (Chemical Engineering Journal, 2024)

27-Hydroxycholesterol inhibits trophoblast fusion during placenta development by activating PI3K/AKT/mTOR signaling pathway - Xiaoyan Zhao; Xiaxia Cai; Haiyan Zhu; Qinyu Dang; Qian Yang; Yandi Zhu; Yadi Zhang; Mengling Zhang; Xinyin Jiang; Zhuo Hu; Yuchen Wei; Rong Xiao; et al. (Archives of Toxicology, 2024)

Piezoelectric BaTiO3 nanoparticles as oxidase mimics breaking pH limitation for colorimetric detection of glutathione reductase - Jijun Liu; Dan Yang; Weiling Hu; Na Huang; Yu Rong; Yijuan Long; Huzhi Zheng (Chemical Engineering Journal, 2024)

Parabens and their metabolite in a marine benthic-dominated food web from the Beibu gulf, South China Sea: Occurrence, trophic transfer and health risk assessment - Rong-Gui Zhu; Chang-Gui Pan; Feng-Jiao Peng; Chao-Yang Zhou; Jun-Jie Hu; Kefu Yu (Water Research, 2024)

High internal phase emulsions of ω-3 fatty acids stabilized by fish scale gelatin particles: Application to lipid-enhanced surimi 3D printing - Yuhang Wang; Die Hu; Wei Yue; Juan You; Tao Yin; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Insights into current bio-processes and future perspectives of carbon-neutral treatment of industrial organic wastewater: A critical review - Xinzheng Zhang; Yuqin Fan; Tianwei Hao; Rong Chen; Tao Zhang; Yong Hu; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Environmental Research, 2024)

Integrated electroflocculation-membrane process for pre-concentration of domestic wastewater: Filtration performance, organics recovery and membrane fouling characteristics - Yuan Yang; Weihang Deng; Lulu Zha; Junjie Qiu; Yisong Hu; Yanzheng Liu; Rong Chen (Resources, Conservation and Recycling, 2023)

First principles insights into the interaction mechanism of iron doped thermally activated kaolinite with Cd and Pb pollutants in organic solid waste incineration flue gas - Yang-wen Wu; Rong Guo; Li-juan Sun; Xin-yue Zhou; Jia-le Zhou; Hai-yuan Zhao; Yi-fei Yu; Zhuang Hu; Bin Hu; Ji Liu; Bing Zhang; Li Zhao; et al. (Waste Management, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Polymeric PDI-based photocatalytic nanoarchitectures promoting the performance of thin film composite membrane for forward osmosis water purification - Pin Zhao; Yang Hu; Xiaoqiang An; Rong Ji; Hao Liu; Hui Zhao; Weilong Song; Yuming Dong; Xinhua Wang (Chemical Engineering Journal, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

Blockade of the Dopamine D3 Receptor Attenuates Opioids-Induced Addictive Behaviours Associated with Inhibiting the Mesolimbic Dopamine System - Rong-Rong Hu; Meng-Die Yang; Xiao-Yan Ding; Ning Wu; Jin Li; Rui Song (Neuroscience Bulletin, 2023)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

Synergistic driving effects of risk factors on human brucellosis in Datong City, China: A dynamic perspective from spatial heterogeneity - Li Shen; Ming-hao Sun; Wen-tao Ma; Qing-wu Hu; Chen-xi Zhao; Zu-rong Yang; Cheng-hao Jiang; Zhong-jun Shao; Kun Liu (Science of The Total Environment, 2023)

OsTKPR1 proteins with a single amino acid substitution fail the synthesis of a specific sporopollenin precursor and cause abnormal exine and pollen development in rice - Feng Liu; Huiting Yang; Rong Tang; Wang Wang; Haodong Shen; Mengxue Xu; Tiancheng Hao; Yuanyuan Hu; Yunhui Zhang; Yiqun Bao (Plant Science, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Site-specific Atg13 methylation-mediated autophagy regulates epithelial inflammation in PM2.5-induced pulmonary fibrosis - Jie Ning; Zijie Pei; Mengruo Wang; Huaifang Hu; Meiyu Chen; Qingping Liu; Mengqi Wu; Peihao Yang; Zihan Geng; Jie Zheng; Zhe Du; Wentao Hu; et al. (Journal of Hazardous Materials, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

Seed priming with rutin enhances tomato resistance against the whitefly Bemisia tabaci - Juan Tang; Haowei Shen; Rong Zhang; Fengbo Yang; Jinyu Hu; Jinting Che; Hongyan Dai; Hong Tong; Qingjun Wu; Youjun Zhang; Qi Su (Pesticide Biochemistry and Physiology, 2023)

Nitrogen-containing malodorous gas pollutants emission characteristics and health risk assessment from an A/O wastewater treatment plant - Yufan Dong; Linlin Ma; Yi Peng; Zhanhong Hu; Zongze Xu; Xiancong Jiang; Rong Cheng; Haolin Chen; Qing Yang (Journal of Water Process Engineering, 2023)

Research Progress on the Osteogenesis-Related Regulatory Mechanisms of Human Umbilical Cord Mesenchymal Stem Cells - Zhengqi Hu; Zhiliang Jiang; Shengzi Meng; Rong Liu; Kun Yang (Stem Cell Reviews and Reports, 2023)

HucMSC-EVs Facilitate In Vitro Development of Maternally Aged Preantral Follicles and Oocytes - Ying-Yi Zhang; Weijie Yang; Yi Zhang; Zhanhong Hu; Yingyan Chen; Yerong Ma; Anran Yang; Zhan Shi; Hanjing Zhou; Peipei Ren; Libing Shi; Jiamin Jin; et al. (Stem Cell Reviews and Reports, 2023)
Follicle developmental capacity and oocyte quality decline with advanced maternal age. Extracellular vesicles from human umbilical cord mesenchymal stem cells (HucMSC-EVs) act as a potential therapeutic product in the treatment of age-related ovarian dysfunction. In vitro culture (IVC) of preantral follicles is a useful method for understanding the mechanism of follicle development and is a promising means for improving female fertility. However, whether HucMSC-EVs have beneficial effects on aged follicle development during IVC has not yet been reported. Our research demonstrated that follicular development with single-addition withdrawal of HucMSC-EVs was better than that with continuous treatment with HucMSC-EVs. HucMSC-EVs facilitated the survival and growth of follicles, promoted the proliferation of granulosa cells (GCs), and improved the steroid hormone secretion of GCs during IVC of aged follicles. Both GCs and oocytes could uptake HucMSC-EVs. Moreover, we observed elevated cellular transcription in GCs and oocytes after treatment with HucMSC-EVs. The RNA sequencing (RNA-seq) results further validated that the differentially expressed genes are related to the promotion of GC proliferation, cell communication, and oocyte spindle organization. Additionally, the aged oocytes displayed a higher maturation rate, presented less aberrant spindle morphology, and expressed a higher level of the antioxidant protein Sirtuin 1 (SIRT1) after treatment with HucMSC-EVs. Our findings suggested that HucMSC-EVs can improve the growth and quality of aged follicles and oocytes in vitro through the regulation of gene transcription, which provides evidence for HucMSC-EVs as potential therapeutic reagents to restore female fertility with advanced age. Graphical Abstract

Structure, stability, and potential function of groundwater microbial community responses to permafrost degradation on varying permafrost of the Qinghai-Tibet Plateau - Sining Zhong; Bin Li; Bowen Hou; Xuming Xu; Jinyun Hu; Rong Jia; Shanqing Yang; Shungui Zhou; Jinren Ni (Science of The Total Environment, 2023)

Effects of fuel injection and energy efficiency on the production and environmental parameters of electric arc furnace -heat recovery systems - Bohan Tian; Guangsheng Wei; Hang Hu; Rong Zhu; Hao Bai; Ziming Wang; Lingzhi Yang (Journal of Cleaner Production, 2023)

A novel precoated anaerobic dynamic membrane bioreactor for real domestic wastewater treatment: In-situ formation, filtration performance and characterization of dynamic membrane - Yuan Yang; Weihang Deng; Jingyu Zhang; Mawuli Dzakpasu; Rong Chen; Xiaochang C. Wang; Yisong Hu (Chemical Engineering Journal, 2023)

Screening of pesticides in serum, urine and cerebrospinal fluid collected from an urban population in China - Ke-Xin Zhao; Ming-Yan Zhang; Dan Yang; Rong-Shu Zhu; Zi-Feng Zhang; Ying-Hua Hu; Kurunthachalam Kannan (Journal of Hazardous Materials, 2023)

Di-(2-ethylhexyl) phthalate impairs angiogenesis and hematopoiesis via suppressing VEGF signaling in zebrafish - Yang-Xi Hu; Bo-Wen Hu; Ya-Sha Chen; Hong-Min You; Mei-Rong Bai; Lu-Jun Zhang; Zhi-Fu Guo; Chun Liang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

Lithologic control of soil C:N:P stoichiometry across a climatic gradient in southwest China - Mingming Sun; Rong Yang; Yixin Tang; Dan Xiao; Wei Zhang; Zhihong Xu; Zhihua Shi; Peilei Hu; Hanqing Wu; Kelin Wang (Journal of Soils and Sediments, 2023)

A novel method for detection of ochratoxin A in foods—Co-MOFs based dual signal ratiometric electrochemical aptamer sensor coupled with DNA walker - Yan Guan; Peng-Bin Si; Tong Yang; Yuan Wu; Yun-Hui Yang; Rong Hu (Food Chemistry, 2023)

Dual-functional electrostatic self-assembly nanoparticles enable suppressed defects and improved charge transport in perovskite optoelectronic devices - Hu Zhang; Pengfei Xu; Zhiliang Chen; Hengkai Zhang; Wenlong Shao; Yanhui Li; Jianfeng Yao; Da Rong; Duanwangde Liu; Liangpan Yang; Siliang Wang; Pengbin Gui; et al. (Chemical Engineering Journal, 2023)

Community succession of microbial populations related to C N P S biological transformations regulates product maturity during cow-manure-driven composting - Xin Liu; Xiangmin Rong; Junyan Yang; Han Li; Wang Hu; Yong Yang; Guoliang Jiang; Rusheng Xiao; Xingxiang Deng; Guixian Xie; Gongwen Luo; Jiachao Zhang (Bioresource Technology, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Coassisted carbonization with HCOOK/(HCOO)2Ca for the fabrication of bamboo-derived oxygen-doped porous carbons exhibiting high-performance sorption of diethyl phthalate from aqueous solutions - Fei Gu; Rongting Ji; Qian Sun; Shengcun Chen; Rong Bai; Yuying Shen; Xinran Liu; Yang Song; Jiangang Han; Xin Jiang; Hu Cheng; Jianming Xue (Bioresource Technology, 2023)

Testing of Mode-I Fracture Toughness of Sandstone Based on the Fracturing Mechanism of an Explosion Stress Wave - Dingjun Xiao; Wentao Yang; Chuanju Liu; Rong Hu (Rock Mechanics and Rock Engineering, 2022)

Induced mutation in ELONGATED HYPOCOTYL5 abolishes anthocyanin accumulation in the hypocotyl of pepper - Rong Chen; Can Yang; Hu Gao; Chunmei Shi; Zhiying Zhang; Guangyu Lu; Xinyan Shen; Yaping Tang; Feng Li; Yongen Lu; Bo Ouyang (Theoretical and Applied Genetics, 2022)

Functional divergence of oligoadenylate synthetase 1 (OAS1) proteins in Tetrapods - Xiaoxue Wang; Jiaxiang Hu; Linfei Song; Enguang Rong; Chenghuai Yang; Xiaoyun Chen; Juan Pu; Honglei Sun; Chuze Gao; David W. Burt; Jinhua Liu; Ning Li; et al. (Science China Life Sciences, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Analysis on improvement effect of subgrade by dynamic compaction - Hui Qi; Chenjun Yang; Chao Hu; Yu Rong; Zhanyong Yao; Hongguang Jiang; Kai Yao; Luchuan Chen; Hui Li; Xianfei Teng (Arabian Journal of Geosciences, 2021)

Mystery of methamphetamine-induced autophagosome accumulation in hippocampal neurons: loss of syntaxin 17 in defects of dynein–dynactin driving and autophagosome–late endosome/lysosome fusion - Huaisha Xu; Yuanhui Zhu; Xufeng Chen; Tingyu Yang; Xi Wang; Xu Song; Xuexue Xie; Miaoyang Hu; Lei Jiang; Jie Cheng; Rong Gao; Jun Wang (Archives of Toxicology, 2021)

Reduction of mussel metamorphosis by inactivation of the bacterial thioesterase gene via alteration of the fatty acid composition - Xiao-Meng Hu; Junbo Zhang; Wen-Yang Ding; Xiao Liang; Rong Wan; Sergey Dobretsov; Jin-Long Yang (Biofouling, 2021)

Reconstruction method of irregular seismic data with adaptive thresholds based on different sparse transform bases - Hu Zhao; Tun Yang; Yu-Dong Ni; Xing-Gang Liu; Yin-Po Xu; Yi-Lei Zhang; Guang-Rong Zhang (Applied Geophysics, 2021)

Isolation and identification of antimicrobial metabolites from sea anemone-derived fungus Emericella sp. SMA01 - Yang Yue; Huahua Yu; Rongfeng Li; Linfeng Hu; Song Liu; Rong’e Xing; Pengcheng Li (Journal of Oceanology and Limnology, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Knockdown of Arginyl-tRNA Synthetase Attenuates Ischemia-Induced Cerebral Cortex Injury in Rats After Middle Cerebral Artery Occlusion - Yang Liu; Xue-Bin Hu; Li-Zhi Zhang; Zi Wang; Rong Fu (Translational Stroke Research, 2021)
Some researchers have previously shown that RNAi knockdown of arginyl-tRNA synthetase (ArgRS) before or after a hypoxic injury can rescue animals from death, based on the model organism, C. elegans . However, there has been no study on the application of arginyl-tRNA synthetase knockdown in treating mammalian ischemic stroke, and its potential mechanism and effect on ischemic brain damage are still unknown. Here, we focused on the Rars gene, which encodes an arginyl-tRNA synthetase, and examined the effects of Rars knockdown in a permanent middle cerebral artery occlusion model in rats. To achieve this aim, adult male Sprague-Dawley (SD) rats were given right cerebral cortex injections of short hairpin RNA (shRNA) adenovirus (AV) particles to knock down arginyl-tRNA synthetase, and a non-targeting control (NTC) vector or phosphate-buffered solution served as the controls. After 4 days, the rats were exposed to permanent middle cerebral artery occlusion (pMCAO). Then, the right cerebral cortex level of arginyl-tRNA synthetase was examined, and the effects of the Rars knockdown were evaluated by differences in infarction volume, oxidative stress, blood-brain barrier, mitochondrial function, and glucose metabolism at 1 day and 3 days after MCAO. The injection of shRNA adenovirus particles successfully suppressed the expression of arginyl-tRNA synthetase in the cerebral cortex. We observed an improvement in oxidative stress, mitochondrial function, and glucose utilization and a reduction in brain edema compared with the non-targeting control rats with suppressed expression of arginyl-tRNA synthetase mRNA in the ipsilateral ischemic cortex of the brain. Our findings indicate that knockdown of arginyl-tRNA synthetase in the cerebral cortex exerted neuroprotective effects, which were achieved not only by the improvement of oxidative stress and glucose utilization but also by the maintenance of mitochondrial morphological integrity and the preservation of mitochondrial function. Knockdown of ArgRS administration could be a promising approach to protect ischemic stroke.

Genetic diversity analysis for narrow-leafed lupin (Lupinus angustifolius L.) by SSR markers - Yishan Ji; Rong Liu; Jinguo Hu; Yuning Huang; Dong Wang; Guan Li; Md. Mosiur Rahman; Hongyan Zhang; Chenyu Wang; Mengwei Li; Tao Yang; Xuxiao Zong (Molecular Biology Reports, 2020)

Network parameters quantify loss of assemblage structure in human‐impacted lake ecosystems - Rong Wang; John A. Dearing; C. Patrick Doncaster; Xiangdong Yang; Enlou Zhang; Peter G. Langdon; Hui Yang; Xuhui Dong; Zhujun Hu; Min Xu; Yanjie Zhao; Ji Shen (Global Change Biology, 2019)
Lake biodiversity is an incomplete indicator of exogenous forcing insofar as it ignores underlying deformations of community structure. Here, we seek a proxy for deformation in a network of diatom assemblages comprising 452 species in 273 lakes across China. We test predictions from network theory that nodes of similar type will tend to self‐organize in an unstressed system to a positively skewed frequency distribution of nodal degree. The empirical data reveal shifts in the frequency distributions of species associations across regions, from positive skew in lakes in west China with a history of low human impacts, to predominantly negative skew amongst lakes in highly disturbed regions in east China. Skew values relate strongly to nutrient loading from agricultural activity and urbanization, as measured by total phosphorus in lake water. Reconstructions through time show that positive skew reduces with temporal intensification of human impacts in the lake and surrounding catchments, and rises as lakes recover from disturbance. Our study illustrates how network parameters can track the loss of aquatic assemblage structure in lakes associated with human pressures.

Regulation of growth performance and lipid metabolism in juvenile grass carp (Ctenopharyngodon idella) with honeysuckle (Lonicera japonica) extract - Xiao-Lin Meng; Zhen-Xiang Zhu; Rong-Hua Lu; Shuai Li; Wen-Pan Hu; Chao-Bin Qin; Xiao Yan; Guo-kun Yang; Guo-Xing Nie (Fish Physiology and Biochemistry, 2019)

Endophytic Pseudomonas fluorescens induced sesquiterpenoid accumulation mediated by gibberellic acid and jasmonic acid in Atractylodes macrocephala Koidz plantlets - Hu-Rong Yang; Jie Yuan; Lian-Hong Liu; Wei Zhang; Fei Chen; Chuan-Chao Dai (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

An integrated prevention strategy to address problems associated with continuous cropping of watermelon caused by Fusarium oxysporum - Fu-Yan Liu; Qiang Zhu; Hu-Rong Yang; Jun Zhou; Chuan-Chao Dai; Xing-Xiang Wang (European Journal of Plant Pathology, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Genome-wide detection of additional fetal chromosomal abnormalities by cell-free DNA testing of 15,626 consecutive pregnant women - Hong Yao; Ya Gao; Jia Zhao; Rong Zhang; Huixin Xu; Huamei Hu; Yanmei Luo; Yuying Yuan; Meili Fu; Hongyun Zhang; Hui Jiang; Wei Wang; et al. (Science China Life Sciences, 2019)

Identification of Carassius auratus gibelio liver cell proteins interacting with the GABAA receptor γ2 subunit using a yeast two-hybrid system - Rong-Rong Ma; Jing Sun; Wen-Hong Fang; Ya-Ping Dong; Ji-Ming Ruan; Xian-Le Yang; Kun Hu (Fish Physiology and Biochemistry, 2019)

Molecular and morphological data reveals new insights into genetic diversity and population structure of Chinese cherry (Prunus pseudocerasus Lindl.) landraces - Tao Chen; Yue-yang Hu; Qing Chen; Yan Wang; Jing Zhang; Hao-ru Tang; Xiao-rong Wang (Genetic Resources and Crop Evolution, 2018)

Evaluating tacrolimus pharmacokinetic models in adult renal transplant recipients with different CYP3A5 genotypes - Can Hu; Wen-jun Yin; Dai-yang Li; Jun-jie Ding; Ling-yun Zhou; Jiang-lin Wang; Rong-rong Ma; Kun Liu; Ge Zhou; Xiao-cong Zuo (European Journal of Clinical Pharmacology, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Exosomal miR-9 Released from HIV Tat Stimulated Astrocytes Mediates Microglial Migration - Lu Yang; Fang Niu; Honghong Yao; Ke Liao; Xufeng Chen; Yeonhee Kook; Rong Ma; Guoku Hu; Shilpa Buch (Journal of Neuroimmune Pharmacology, 2018)

Design, synthesis and anti-cancer evaluation of novel podophyllotoxin derivatives as potent tubulin-targeting agents - Cui Hu; Xiang Zhu; Gu-Hao Wang; Xun Wu; Hong-Wei Han; Gui-Hua Lu; Jin-Liang Qi; Yan-Jun Pang; Rong-Wu Yang; Xiao-Ming Wang; Yong-Hua Yang (Medicinal Chemistry Research, 2018)

Erratum to: Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Repeated pre-training sleep restriction in adolescent rats impaired spatial performance - Su-Rong Yang; Huan-Xin Sun; Zhen-Zhen Hu; Si-Heng Wang; Hui Sun; Yin-Jia Xue; Chen-Bo Ye (Sleep and Biological Rhythms, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Neurofibromin Regulates Seizure Attacks in the Rat Pilocarpine-Induced Model of Epilepsy - Min Ren; Kunyi Li; Dan Wang; Jiamei Guo; Jing Li; Guang Yang; Xianghua Long; Wenjing Shen; Rong Hu; Xuefeng Wang; Kebin Zeng (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

The composition of pericarp, cell aging, and changes in water absorption in two tomato genotypes: mechanism, factors, and potential role in fruit cracking - Zeen Yang; Zhen Wu; Chuan Zhang; Enmei Hu; Rong Zhou; Fangling Jiang (Acta Physiologiae Plantarum, 2016)

Strawberry MOTHER OF FT AND TFL1 regulates seed germination and post-germination growth through integrating GA and ABA signaling in Arabidopsis - Yang Hu; Yu-Rong Gao; Wei Wei; Kai Zhang; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

A highly efficient grapevine mesophyll protoplast system for transient gene expression and the study of disease resistance proteins - Feng-Li Zhao; Ya-Juan Li; Yang Hu; Yu-Rong Gao; Xue-Wen Zang; Qin Ding; Yue-Jin Wang; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Validation of cross-contamination control in biological safety cabinet for biotech/pharmaceutical manufacturing process - Shih-Cheng Hu; Angus Shiue; Jin-Xin Tu; Han-Yang Liu; Rong-Ben Chiu (Environmental Science and Pollution Research, 2015)

The Effect of PSD-93 Deficiency on the Expression of Early Inflammatory Cytokines Induced by Ischemic Brain Injury - Qingxiu Zhang; Hongyu Cheng; Rong Rong; Hui Yang; Qiuhong Ji; Qingjie Li; Liangqun Rong; Gang Hu; Yun Xu (Cell Biochemistry and Biophysics, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

Molecular cloning and functional characterization of the hepcidin gene from the convict cichlid (Amatitlania nigrofasciata) and its expression pattern in response to lipopolysaccharide challenge - Jing-Ruei Chi; Long-Si Liao; Rong-Guang Wang; Chu-Sian Jhu; Jen-Leih Wu; Shao-Yang Hu (Fish Physiology and Biochemistry, 2015)

Heme Oxygenase-2 Suppress TNF-α and IL6 Expression via TLR4/MyD88-Dependent Signaling Pathway in Mouse Cerebral Vascular Endothelial Cells - Ren-Jin Chen; Hong-Hua Yuan; Teng-Ye Zhang; Zhen-Zhen Wang; An-kang Hu; Lian-Lian Wu; Zhang-Ping Yang; Yong-Jiang Mao; De-Jun Ji; Xiao-Rong Zhu (Molecular Neurobiology, 2014)

Hepatocellular Carcinoma in Budd-Chiari Syndrome: Enhancement Patterns at Dynamic Gadolinium-Enhanced T1-Weighted MR Imaging - Chun Yang; Kai Xu; Junnian Zheng; Ping Ma; Chunfeng Hu; Shaodong Li; Yutao Rong; Xin Lu; Qingqiao Zhang; Maoheng Zu; Rong Hua; Ling Zhang (Cell Biochemistry and Biophysics, 2014)

Two new bicyclic sesquiterpenes from the stems of Kadsura heteroclita - Wei Su; Jian-Ping Zhao; Jian Hu; Min Yang; Melissa Jacob; Xiong Cai; Rong Zeng; Sheng-Huang Chen; Hui-Yong Huang; Ikhlas Khan; De-An Guo; Wei Wang (Natural Product Research, 2014)

A Proteomic Analysis of Placental Trophoblastic Cells in Preeclampsia–Eclampsia - Kaidong Ma; Hong Jin; Rong Hu; Yu Xiong; Shufeng Zhou; Peng Ting; Yan Cheng; Yan Yang; Pengyuan Yang; Xiaotian Li (Cell Biochemistry and Biophysics, 2014)

What interests them in the pictures? — Differences in eyetracking between rhesus monkeys and humans - Ying-Zhou Hu; Hui-Hui Jiang; Ci-Rong Liu; Jian-Hong Wang; Cheng-Yang Yu; Synnöve Carlson; Shang-Chuan Yang; Veli-Matti Saarinen; Joshua D. Rizak; Xiao-Guang Tian; Hen Tan; Zhu-Yue Chen; et al. (Neuroscience Bulletin, 2013)

Gorham-Stout syndrome in mainland China: a case series of 67 patients and review of the literature - Po Hu; Xiang-gui Yuan; Xin-yang Hu; Fa-rong Shen; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Effect of sand-stabilizing shrubs on soil respiration in a temperate desert - Zhi-Shan Zhang; Xin-Rong Li; Robert S. Nowak; Pan Wu; Yan-Hong Gao; Yang Zhao; Lei Huang; Yi-Gang Hu; Rong-Liang Jia (Plant and Soil, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Provenance and tectonic setting of Neoproterozoic sedimentary sequences in the South China Block: evidence from detrital zircon ages and Hf–Nd isotopes - Wei Wang; Fukun Chen; Rong Hu; Yang Chu; Yi-Zeng Yang (International Journal of Earth Sciences, 2012)

Genomic rearrangement between wheat and Thinopyrum elongatum revealed by mapped functional molecular markers - Li-Jun Hu; Cheng Liu; Zi-Xian Zeng; Guang-Rong Li; Xiao-Jin Song; Zu-Jun Yang (Genes & Genomics, 2012)

Tongxinluo promotes mesenchymal stem cell tube formation in vitro - Xin-yang Hu; Wen-xia Wang; Min-jia Yu; Xian-bao Liu; Rong-rong Wu; Feng Gao; Xin Huang; Jiang Cao; Xiao-jie Xie; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular characterization of a wheat -Thinopyrum ponticum partial amphiploid and its derived substitution line for resistance to stripe rust - Li-Jun Hu; Guang-Rong Li; Zi-Xian Zeng; Zhi-Jian Chang; Cheng Liu; Zu-Jun Yang (Journal of Applied Genetics, 2011)

Satellite altimeter observations of nonlinear Rossby eddy–Kuroshio interaction at the Luzon Strait - Quanan Zheng; Chang-Kuo Tai; Jianyu Hu; Hongyang Lin; Rong-Hua Zhang; Feng-Chun Su; Xiaofeng Yang (Journal of Oceanography, 2011)

Molecular cytogenetic identification of a new wheat-Thinopyrum substitution line with stripe rust resistance - Li-Jun Hu; Guang-Rong Li; Zi-Xian Zeng; Zhi-Jian Chang; Cheng Liu; Jian-Ping Zhou; Zu-Jun Yang (Euphytica, 2011)

A genome-wide association analysis implicates SOX6 as a candidate gene for wrist bone mass - LiJun Tan; Rong Liu; ShuFeng Lei; Rong Pan; TieLin Yang; Han Yan; YuFang Pei; Fang Yang; Feng Zhang; Feng Pan; YinPin Zhang; HongGang Hu; et al. (Science China Life Sciences, 2010)

Chewing substances with or without tobacco and risk of cardiovascular disease in Asia: a meta-analysis - Li-na Zhang; Yun-mei Yang; Zhe-rong Xu; Qi-feng Gui; Qin-qing Hu (Journal of Zhejiang University-SCIENCE B, 2010)

Soil organic carbon and nitrogen stocks in an age-sequence of poplar stands planted on marginal agricultural land in Northeast China - Rong Mao; De-Hui Zeng; Ya-Lin Hu; Lu-Jun Li; Dan Yang (Plant and Soil, 2010)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Heregulin protects mesenchymal stem cells from serum deprivation and hypoxia-induced apoptosis - Chun Gui; Jian An Wang; Ai Na He; Tie Long Chen; Rong Hua Luo; Jun Jiang; Xin Yang Hu; Xiao Jie Xie (Molecular and Cellular Biochemistry, 2007)

Bone marrow mesenchymal stem cell transplantation combined with perindopril treatment attenuates infarction remodelling in a rat model of acute myocardial infarction - Jian-an Wang; Rong-hua Luo; Xing Zhang; Xiao-jie Xie; Xin-yang Hu; Ai-na He; Jie Chen; Jia-hui Li (Journal of Zhejiang University-SCIENCE B, 2006)

Comparison of (−)-Epigallocatechin-3-Gallate Elicited Liver and Small Intestine Gene Expression Profiles Between C57BL/6J Mice and C57BL/6J/Nrf2 (−/−) Mice - Guoxiang Shen; Changjiang Xu; Rong Hu; Mohit R. Jain; Sujit Nair; Wen Lin; Chung S. Yang; Jefferson Y. Chan; A.-N. Tony Kong (Pharmaceutical Research, 2005)

Inheritance of the Triple-spikelet Character in a Tibetan Landrace of Common Wheat - Wu-Yun Yang; Bao-Rong Lu; Xiao-Rong Hu; Yi Yu; Yong Zhang (Genetic Resources and Crop Evolution, 2005)

Inheritance in hexaploid wheat of genes for hairy auricles and hairy leaf sheath derived from Aegilops tauschii Coss. - Yang Wu-Yun; Wu Bei-Hua; Hu Xiao-Rong; Ye Yi; Zhang Yong (Genetic Resources and Crop Evolution, 1999)